PROCEDURAL FEATURES OF EVIDENCE COLLECTION AT THE STAGE OF PRELIMINARY INVESTIGATION - Muhammadievich, Usmonov Vosid; Shermamatovna, Holiqova Nargiza; talabasi, guruh (Research Focus International Scientific Journal, 2026)
This article examines the theoretical and practical aspects of evidence collection at the stage of preliminary investigation, which is considered an important phase of criminal procedural law. The procedural framework for collecting evidence, its legal foundations, the rights and obligations of participants, and the role of this process in ensuring a fair resolution of a criminal case are analyzed.